2023
DOI: 10.1039/d2sm01693a
|View full text |Cite
|
Sign up to set email alerts
|

Lipid vesicles induced ordered nanoassemblies of Janus nanoparticles

Abstract: Since many advanced applications require specific assemblies of nanoparticles (NPs), considerable efforts have been made to fabricate nanoassemblies with specific geometries. Although nanoassemblies can be fabricated through top-down approaches, recent...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 52 publications
3
27
0
Order By: Relevance
“…This hexagonal lattice is simply the asymptotic limit of the highly ordered nanoassemblies of Janus NPs on lipid vesicles, recently observed by us. 40 There, we found that the JNPs self-assemble into highly ordered polyhedra on vesicles, including three Platonic solids, with geometries that satisfy the upper limit of Euler's polyhedral formula.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…This hexagonal lattice is simply the asymptotic limit of the highly ordered nanoassemblies of Janus NPs on lipid vesicles, recently observed by us. 40 There, we found that the JNPs self-assemble into highly ordered polyhedra on vesicles, including three Platonic solids, with geometries that satisfy the upper limit of Euler's polyhedral formula.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, eight and 20 JNPs do not self-assemble into their respective Platonic solids corresponding to the cube and dodecahedron since these polyhedra do not obey the upper limit of Euler's polyhedral formula. 40 Furthermore, we showed that the geometries of these nanoclusters are preserved for a given number of JNPs as the vesicle's diameter, D LV , is increased, albeit the degree of fluctuations increases with D LV . 40 The present work extends our recent study 40 to the limit of a large number of JNPs adhering to tensionless planar membranes as a function of the JNPs' number density and adhesion energy density.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…45 In addition, for vesicles and lipid-wrapped nanoparticles, their fluid/gel transition temperature decreases with decreasing size, which has been demonstrated by simulation or experiment. [46][47][48][49][50][51] This is because the destruction of gel packing is induced by decreasing the size, moving its free energy closer to that of the fluid. It is known that the nanomaterials have a higher Gibbs free energy due to the more and more significance of the surface as the reduces size.…”
Section: Resultsmentioning
confidence: 99%